2013
DOI: 10.1074/jbc.m113.472076
|View full text |Cite
|
Sign up to set email alerts
|

The HECT Type Ubiquitin Ligase NEDL2 Is Degraded by Anaphase-promoting Complex/Cyclosome (APC/C)-Cdh1, and Its Tight Regulation Maintains the Metaphase to Anaphase Transition

Abstract: Background: NEDL2 is a member of the HECT type ubiquitin ligase NEDD4 family, but its function remains largely unknown. Results: NEDL2 is degraded by APC/C-Cdh1 during mitotic exit and regulates metaphase to anaphase transition. Conclusion: NEDL2 appears to dynamically modulate regulation of mitosis. Significance: Our data provide a novel substrate of APC/C-Cdh1 and reveal an additional protein by which HECT type ubiquitin ligase can regulate mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…The HECW2 gene is a HECT-type ubiquitin ligase and is known to regulate the stability of p73. 27 The DNM in our study was identified in the Homologous to the E6-AP Carboxyl Terminus (HECT) domain of the protein. Out of the five previously reported mutations, four were located in exons associated with the HECT domain, which displays a lower number of non-synonymous mutations in the general population (figure 2).…”
Section: Trio Sequencingmentioning
confidence: 79%
See 1 more Smart Citation
“…The HECW2 gene is a HECT-type ubiquitin ligase and is known to regulate the stability of p73. 27 The DNM in our study was identified in the Homologous to the E6-AP Carboxyl Terminus (HECT) domain of the protein. Out of the five previously reported mutations, four were located in exons associated with the HECT domain, which displays a lower number of non-synonymous mutations in the general population (figure 2).…”
Section: Trio Sequencingmentioning
confidence: 79%
“…Of genes previously not implicated in neurodevelopmental disorders we find that DNMs in the gene HECW2, identified in one of our trios, has also been identified in patients in five previous studies, while no DNMs have been found in controls. Among the previously reported variants in HECW2 all had a CADD score >15 (range [15][16][17][18][19][20][21][22][23][24][25][26][27]. To more formally evaluate the finding of DNMs in HECW2 in our trios and previous studies, we used the statistical framework developed by Samocha et al 14 Using the 5338 trio families collated above together with our 39 trios yields an expected number of DNMs (non-synonymous and stopgains) in HECW2 of 0.7, while we observed a total of six nonsynonymous mutations ( p-value = 6.11×10 e-5 ).…”
Section: Trio Sequencingmentioning
confidence: 98%
“…Increased NEDL2 mRNA and protein levels were reported in colon and cervix tumor tissues [147]. Existing evidence implicates NEDL2 in mitosis.…”
Section: Nedls/hecwsmentioning
confidence: 97%
“…It was shown that NEDL2 associates with the mitotic spindle, and its protein level peaks during mitosis. Depletion of NEDL2 prolongs metaphase, while overexpression induces chromosomal lagging [147]. Probing of NEDL2's interactome has identified a panel of mitotic proteins as NEDL2 interactors, including an activator of the anaphase-promoting complex/cyclosome (APC/C) -Cdh1.…”
Section: Nedls/hecwsmentioning
confidence: 99%
See 1 more Smart Citation